1960
DOI: 10.1099/00221287-23-2-243
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Mate-Killer (mu) particles in Paramecium aurelia, stock 540

Abstract: SUMMARYThe mate-killer (mu) particles in the cytoplasm of Paramecium aurelia, stock 540, variety (syngen) 1, were studied by : Feulgen-staining ; phase-contrast microscopy ; fluorescence under ultraviolet irradiation after staining with acridine orange ; electron microscopy (including the ' silver-Feulgen ' technique). The appearance of the particles following treatment with DNAase and RNAase was observed. It was found that the mu particles were capsulated rod-shaped structures, 2-lop long and about 0 . 3 ,~ i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1961
1961
1978
1978

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 4 publications
1
23
0
Order By: Relevance
“…A number of endosymbionts of Paramecium aiirelia occur in vesicles (Beale et al 1969;Stevenson, 1970)~ but kappa symbionts normally do not. Vesicles of various types, some of which have digestive function, are common in the cytoplasm of P. aurelia (Jurand & Selman, 1969), SO symbionts might be digested in this way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of endosymbionts of Paramecium aiirelia occur in vesicles (Beale et al 1969;Stevenson, 1970)~ but kappa symbionts normally do not. Vesicles of various types, some of which have digestive function, are common in the cytoplasm of P. aurelia (Jurand & Selman, 1969), SO symbionts might be digested in this way.…”
Section: Discussionmentioning
confidence: 99%
“…Cell numbers were counted by removing cells one by one from a sample of culture; symbiont numbers were counted by taking representative fields of random cells prepared by the Os0,-lactoorcein method (Beale & Jurand, 1966) and counting symbionts with the aid of a squared grid in the ocular. Symbionts bearing R bodies ('large') may be distinguished from those not having R bodies small') by their different size (particularly breadth) and the fact that large forms stain more intensely.…”
Section: Bacterial Endosymbiosis In Parameciummentioning
confidence: 99%
“…Light microscopy revealed that they had the size and shape of bacteria, and they occurred in numbers from 100 to 1000 per cell, depending on the type of particle. Studies with the electron microscope showed that they consist of a double membrane and granular internal contents (Jurand and Preer, 1968;Beale and Jurand, 1960). These granules were approximately the size of ribosomes (Jurand and Preer, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…These macromolecules have been reported to be present in situ, using cytochemical techniques (Beale and Jurand, 1960). Also, specific enzymes have been shown to be present in isolated particles, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…To observe the symbionts in situ two methods were used. In the first, whole paramecia were observed with a dark phase-contrast microscope (Carl Zeiss), using paramecia treated with lactoorcein according to the method of Beale & Jurand (1966). In the second, I p Araldite sections were mounted on slides, stained with toluidine blue and observed with ordinary bright-field microscopy.…”
mentioning
confidence: 99%